Economic Viability Analysis of an Oral Anthelmintic Treatment for Cattle in Feedlot - Nakatani, Matheus Takemi Muchon; Conde, Mario Henrique; Freitas, Mariana Green de; Fávero, Flávia Carolina; Paula, Lucas Chaves de; Cabrera, Marcos Da Silva; Gomes, Marina de Nadai Bonin; Brumatti, Ricardo Carneiro; Rodrigues, Daniel de Castro; Borges, Fernando de Almeida (Journal of Agricultural Studies, 2021)
The economic viability of a commercial oral anthelmintic suspension containing 10% fenbendazole was evaluated in Angus x Nelore cattle in a feedlot. Two groups of 37 animals (treated and non-treated) were formed. A random-block design was used based on initial weight, egg count per gram of feces (EPG) and carcass grade. EPG counts and the determination of weight were performed on Days 0, 42 and 122. Carcass grade and yield were determined on the day of slaughter. Economic viability was evaluated using cost-effectiveness, sensitivity and financial analyses, considering three economic scenarios: most likely (M), optimistic (O) and pessimistic (P). The anthelmintic achieved 99.89% efficacy regarding EPG reduction. The animals exhibited an increase of 20.7 kg in live weight, 20.2 kg in live weight gain and 0.166 kg in daily weight gain (p < 0.05). No effects were found on yield or carcass grade (p > 0.05). The genus Haemonchus predominated at the onset of the study, whereas only the genus Cooperia was found after treatment. A net return of 14.60 USD per animal was found in the treated group, which remained viable under O, M and P scenarios, with respective differences of 18.92%, 12.86% and 91.15% in gross profit. The treatment was financially superior under all scenarios (real, M, O and P), with reductions of 1.89, 1.04, 0.48 and 16.39 years for the recovery of the initial investment. These results demonstrate the importance of economic analysis methods in the evaluation and selection of anthelmintics.